Dreamtime Superhighway (TA27) Sydney Basin Rock Art and Prehistoric Information Exchange - McDonald, Jo (Terra Australis, 2008)
Dreamtime Superhighway presents a thorough and original contextualization of the rock art and archaeology of the Sydney Basin. By combining excavation results with rock art analysis it demonstrates that a true archaeology of rock art can provide insights into rock art image-making in people's social and cultural lives. Based on a PhD dissertation, this monograph is a significantly revised and updated study which draws forcefully on rich and new data from extensive recent research-much of it by McDonald herself. McDonald has developed a model that suggests that visual culture-such as rock artmaking and its images and forms-could be understood as a system of communication, as a way of signaling group identifying behaviour. For the archaeologist of art, the anthropologist of art and those of us who try to think about past worlds... this monograph is a must read.